Pengaruh Rasio Kemandirian, Rasio Efektivitas Dan Rasio Efisiensi Terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota Di Sumatera Barat - rahma dona; anne putri (Indonesian Journal of Innovation Science and Knowledge, 2026)
This study aims to analyze the effect of the independence ratio, effectiveness ratio, and efficiency ratio on the financial performance of regency and municipal governments in West Sumatra Province during the 2021–2024 period. This research employs a quantitative approach with an associative research design. The data used are secondary data obtained from the Regional Budget Realization Reports published by the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia. The sample consists of 10 regency and municipal governments selected using purposive sampling, resulting in 40 observations. Data were analyzed using multiple linear regression with the assistance of SPSS, preceded by classical assumption tests and followed by t-test, F-test, and coefficient of determination analysis. The results show that the independence ratio has a negative and significant effect on financial performance, while the effectiveness ratio has no significant effect on financial performance. Meanwhile, the efficiency ratio has a positive and significant effect on financial performance. Simultaneously, the independence ratio, effectiveness ratio, and efficiency ratio have a significant effect on local government financial performance. The Adjusted R Square value of 0.906 indicates that the three independent variables explain 90.6% of the variation in financial performance, while the remaining 9.4% is explained by other factors outside the research model.